A Good Man is Easy to Find: Flannery O’Connor’s Theology of Death - João Pedro Vala (University of Chitral Journal of Linguistics and Literature, 2024)
The aim of this paper is to describe Flannery O’Connor’s stories as the repetitionof a pattern that consists in, through sickness, changing good country people intogood men. Therefore, sickness, in O’Connor’s oeuvre, has to be described as ablessing, an idea that the writer herself would gladly approve of. To prove it, thispaper takes into consideration the way O’Connor described the debilitating diseasethat would end up by killing her. The usual portrait critics make of O’Connor’swork consists in randomly applying catchwords like South, Catholic or Grotesque.Contrarily to these critics’ description, the somehow systematic approach toO’Connor’s stories here proposed does not in any way serve to reduce and simplifythe writer’s work, but to enhance its mystery and manners. What this paper tries todemonstrate is that, through the analysis of the plot of O’Connor’s short stories, wecan have access to her personal theology. A theology that, although pictured soghastly in tales full of rapes, delusions and murders, is profoundly optimistic.O’Connor’s aim as a writer is, thence, to prove that redemption and revelations areonly dependent of an awareness regarding our own death, an awareness onlysickness, in its many forms, can bring.